Implementación De Un Sistema Tecnificado Por Hidroponía Para Cultivos Hortícolas En La Universidad Técnica De Cotopaxi Extensión La Maná. - Cordova Heredia, Dennis Alexander (2022)
In this project we designed and implemented an automated system for agriculture with hydroponic technology, to start the process of a technified system for hydroponics we have in mind the place where it will be installed, in this case it is located in block b of the Technical University of Cotopaxi extension La Maná, a greenhouse was built for protection against different climates that may affect the system, Once the greenhouse is finished we continue with the construction of the hydroponic system this was done with water pipes for water flow, in the construction of the control board for automation is used a PLC P1AM 100, everything is carried out with the research conducted in both physical and digital books, field visits among others. The hydroponic system is a very effective way of cultivation without soil and in smaller spaces with the same production as it would have in large spaces.